Location Evaluation for Implementation of Vlc, in Chile - Soto-Gomez, J; Alfaro-Marchant, M; Carrasco-Armijo, R; Gonzalez-Ortega, A (Institute of Electrical and Electronics Engineers Inc., 2018)
This research focuses on making a decision with multiple criteria about the ideal location of visible light implementation VLC in Chile. VLC is a wireless communication system that uses visible light as a means of data transmission, becoming an alternative for radio frequency systems, especially the use of WI-FI. In relation to the decision making that is required, there are several alternatives, seeking as a result to make a single decision. During the decision-making process of the implementation, physical arguments of the geography are weighted, among other significant variables, based on one of the multicriteria methods in decision-making called ELECTRA I, used on variables that are qualified and subsequently limits of comparison, as a way to help the selection of characterized alternatives. As a main characteristic, evaluate the relative advantages and disadvantages among the alternatives according to the criteria that are the object of analysis and give a certain hierarchy with preference orders. © 2018 IEEE.